Representasi Timur (The Orient) Dalam Video Klip Coldplay “Hymn For The Weekend” - Lina Andriani; Agusly Irawan Aritonang; Chory Angela Wijayanti (Jurnal e-Komunikasi, 2018)
Video clip “Hymn For The Weekend” was made by Coldplay released in 2016. In the video clip Coldplay takes India as the background for the shoot. Coldplay is a group of British bands who describes orientalism in India, which also once a British colony through the video clip